A Novel Electrochemical Sensor Based on Silver Nanodendrites and Molecularly Imprinted Polymers for the Determination of Tetrabromobisphenol A in Water. Issue 12 (22nd October 2018) - Xu, Wanzhen; Zhang, Kun; Wang, Ningwei; Liu, Tao; Huang, Weihong; Liu, Tianshu; Lu, Yi; Yang, Wenming; Li, Songjun
Abstract: A novel and facile electrochemical sensor based on three different modification layers was prepared to detect tetrabromobisphenol A (TBBPA). They included tetracyanoquinodimethane (TCNQ), silver nanodendrites (AgNDs) and molecularly imprinted polymers (MIPs). TCNQ − acts as inducer can be reacted with Ag + to form Ag‐TCNQ fibers and then constructed the nanodendritic structures. The latter two modification layers were synthesized on electrode by‐ways of electrodeposition and electropolymerization respectively. AgNDs has excellent conductivity and large specific surface area, which has good potential to be used as a bridge between electrode and MIPs. It can considerably improve the sensitivity of the sensor and provide immense deposit sites to pyrrole. MIPs synthesized using electropolymerization can firmly get attach on electrode, thereby, providing polymers with stable imprinted cavities and having the possibility to be reused. Under optimum conditions, the concentration of TBBPA exhibited an excellent linear relationship between 5.0×10 −9 and 1.0×10 −5 mol L −1, with a limit of dectection of 2.54×10 −10 mol L −1 (S/N=3). The reproducibility of the sensor was observed to be 3.42 % and was immune to analogues. Finally the sensor was successfully applied to actual water samples. Abstract :